Implementation of Divorce Mediation for State Civil Apparatus: Sociological Analysis of Islamic Law - Arisman, Arisman; Yusrial, Yusrial; Umar, Abdullah (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Divorce mediation has become one of the alternative dispute resolutions recognized in the Indonesian legal system. However, its application in the State Civil Apparatus has its own challenges that require in-depth analysis. This research aims to propose to the government and the courts that mediation for the state civil apparatus be carried out during the process of obtaining a superior's license by a mediator appointed and approved by the local government so that after the superior's license is issued, the mediation process is no longer carried out in court. This research uses a qualitative method with a juridical-sociological approach, data sources are taken through primary and secondary data, in the form of data from four religious courts in one of the provinces in Indonesia. All data were analyzed using the Milles & Hubberman Interactive Model Analysis. The results of the study were threefold: First, the implementation of mediation is not yet optimal, second, the recommendation to appoint a competent mediator team, third, the proposal to adopt the results of mediation into the trial. This study recommends increasing mediator training and psychological support for the State Civil Apparatus involved as a form of wider socialization of the benefits of mediation.